ADP-Ribosylation Reactions: From Bacterial Pathogenesis to Cancer 1999
DOI: 10.1007/978-1-4419-8740-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NAD:arginine ADP-ribosyltransferases

Abstract: NAD:arginine mono-ADP-ribosyltransferases catalyze the transfer of ADP-ribose from NAD to the guanidino group of arginine on a target protein. Deduced amino acid sequences of one family (ART1) of mammalian ADP-ribosyltransferases, cloned from muscle and lymphocytes, show hydrophobic amino and carboxyl termini consistent with glycosylphosphatidylinositol (GPI)-anchored proteins. The proteins, overexpressed in mammalian cells transfected with the transferase cDNAs, are released from the cell surface with phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We treated AsPC-1 and BxPC-3 cells with PI-PLC. PI-PLC treatment is a well established assay to determine whether a protein is GPI-anchored or not (11,41). Using mAb 4H2, we found that although the PrP on the cell surface of BxPC-3 was highly resistant to PI-PLC, the PrP on the surface of AsPC-1 was much more susceptible to identical treatment ( Fig.…”
Section: Prp From Aspc-1 But Not Bxpc-3 Is Sensitive To Pi-plc Treatmmentioning
confidence: 89%
“…We treated AsPC-1 and BxPC-3 cells with PI-PLC. PI-PLC treatment is a well established assay to determine whether a protein is GPI-anchored or not (11,41). Using mAb 4H2, we found that although the PrP on the cell surface of BxPC-3 was highly resistant to PI-PLC, the PrP on the surface of AsPC-1 was much more susceptible to identical treatment ( Fig.…”
Section: Prp From Aspc-1 But Not Bxpc-3 Is Sensitive To Pi-plc Treatmmentioning
confidence: 89%
“…MARylation was identified decades ago as a protein, post-translational modification (PTM) exploited by bacterial toxins to promote bacterial pathogenesis in host cells (Gill et al, 1969;Moss and Vaughan, 1977). While the occurrence of this protein PTM in mammalian cells has soon become evident (Dani et al, 2011;Jones and Baird, 1997;Lupi et al, 2000;Lupi et al, 2002;Moss et al, 1999;Okazaki and Moss, 1996;Seman et al, 2004) only recently, with the definition of the different PARPs (and of their intrinsic enzymatic activities) the physiological functions the MARylating PARPs may regulate are emerging (Cohen and Chang, 2018;Gupte et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mono-ADP-ribosylation is a type of protein posttranslational modification (PTM), which can trans fer a single ADP-ribose from nicotin amide adenine dinucleotide (NAD + ) to the specific amino-acids residues of target proteins (Zolkiewska et al 1992;Moss et al 1999). PTM plays an important role in various physiological and pathophysiological processes, such as DNA repair, transcription, cell cycle regulation, signal transduc tion, necrosis and apoptosis (Hassa et al 2006).…”
Section: Introductionmentioning
confidence: 99%